(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software reliability is a significant quality characteristic, and reliability models are often used to gauge and anticipate programming development. The quality of versatile apps conditions contrasts from that of PC and server conditions because of numerous elements, like the organization, energy, battery, and similarity. Assessing and anticipating versatile application dependability are genuine difficulties in light of the variety of the portable conditions in which the applications are utilized, and the absence of openly accessible deformity information. Also, bug reports are alternatively put together by end-clients. In the current research work, in view of the writing survey and specialist’s assessment working in the field of versatile application advancement, 10 reliability leading factors and 14 sub-factors have been recognized that are fundamental for evaluating reliability of a portable applications.